“Devemos fazer esta guerra?” : o aconselhamento político na corte de D. Duarte (1433-1438) - Silva, Êmily Sthephane Rodrigues da (2024)
The research analyzes political advice at the court of the second monarch of the Avis dynasty, D. Duarte (1391-1438). The chronological space the five years of the Edwardian reign (1433-1438), in which the king continued with the forged projects during the reign of his father, D. João I, among these, the war directed at the North African. When observing the advice recorded in one of his works, the Book of Councils of El-Rei D. Duarte, or simply, Livro da Cartuxa, we realize that one of the subjects discussed in the source refers to this war. In this sense, from the perspective of linguistic contextualism, we intend to make contributions to the historiography by analyzing of the language of the agents involved in this consultation.